Individualizacija sportivnoj trenirovki sprinterov c ucetom tipov nejropsichiceskoj reaktivnosti - Drizika, A. G. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The experimental researches, which have been carried out on sprinters of high qualification by the author, have confirmed the necessity of creation of the starting reactance in athletes with the explosive type of cyclic preparedness on the basis of strengthening of stress-factors of the environment. The creation of the starting reactance at athletes with an equal type of cyclic preparedness is more acceptable on the basis of preservation of sparing conditions of the environment at an economical expenditure of the power resources.